AhR governs lipid metabolism: the role of gut microbiota - Zheng, Wanru; Liu, Mengkuan; Lv, Xinyu; He, Cuimei; Yin, Jie; Ma, Jie (Frontiers in Microbiology, 2025)
The Aryl Hydrocarbon Receptor (AhR) is widely present in mammalian bodies, showing high affinity for various exogenous substances such as polycyclic aromatic hydrocarbons (PAHs) and coumarin. Under physiological conditions, AhR mainly participates in regulating the body’s immune response, cell proliferation, and apoptosis among a series of processes. Recent studies have revealed a close connection between AhR and lipid metabolism. The gut microbiota plays a significant role in regulating host lipid metabolism. Growing evidence suggests an inseparable link between gut microbiota and AhR signaling. This review summarizes the relationship between AhR and lipid metabolism disorders, as well as the interaction between gut microbiota and AhR, exploring how this interaction modulates host lipid metabolism.